English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Solve x2 + 7x + 6 = 0 for x

2006-12-29 14:13:48 · 19 answers · asked by Anonymous in Science & Mathematics Mathematics

19 answers

x² + 7x + 6 = 0

(x + 6) (x + 1)

- - - - - - - - -

Roots

x + 6 = 0

x + 6 - 6 = 0 - 6

x = - 6

- - - - -

x + 1 = 0

x + 1 - 1 = 0 - 1

x = - 1

- - - - - - -

x = - 6

or

x = - 1

- - - - - - - -s-

2006-12-30 01:50:12 · answer #1 · answered by SAMUEL D 7 · 1 0

x² + 7x + 6 = 0
x² + 7x = -6
x² + 7x + (7/2)² = -6 + (7/2)²
(x + 7/2)² = -24/4 + 49/4
(x + 7/2)² = 25/4
x + 7/2 = ± 5/2
x = -7/2 + 5/2 or x = -7/2 - 5/2
x = -2/2 or x = -12/2
x = -1 or x = -6

that's completing the square, which always works, but factoring, when it works, is easier.

x² + 7x + 6 = 0
(x + 6)(x + 1) = 0
x + 6 = 0 or x + 1 = 0
x = -6 or x = -1

2006-12-29 14:21:49 · answer #2 · answered by Philo 7 · 1 0

x^2 + 7x + 6 = 0
(x + 1)(x + 6) = 0
(x + 1) = 0 or (x + 6) = 0
x = -1 x = -6

2006-12-29 14:22:13 · answer #3 · answered by stewartlucas467 2 · 1 0

just sustitute

0 x 2 + 7 x 0 + 6 = 20

multiply 2 and 7 by 0 then add the products then add 6!

2006-12-29 14:34:27 · answer #4 · answered by purplelady 2 · 0 0

I assume X2 means X^2 and it is a quadratic equation.
factor or use the quadratic formula
I chose to factor as it factors easily w/o doing a lot of algebra
(X+1)(X+6)=0 therefore:

X= -1
and X= -6

2006-12-29 14:17:24 · answer #5 · answered by beanie_boy_007 3 · 1 0

x^2 + 7x + 6 = 0
(x + 1)(x + 6) = 0
x = -1 or -6

If you aren't certain of an answer, you can always do this.

x = (-b ± sqrt(b^2 - 4ac))/(2a)

x = (-7 ± sqrt(7^2 - 4(1)(6)))/(2(1))
x = (-7 ± sqrt(49 - 24))/2
x = (-7 ± sqrt(25))/2
x = (-7 ± 5)/2
x = (-12/2) or (-2/2)
x = -6 or -1

2006-12-29 14:18:01 · answer #6 · answered by Sherman81 6 · 1 0

x^2 + 7x + 6 = 0
(x+6)(x+1)=0
x+6=0
x=-6
x+1=0
x=-1
x=-6, -1

2006-12-29 14:16:36 · answer #7 · answered by yupchagee 7 · 2 1

x ^2+7x+6
=x^2+x+6x+6
=x(x+1)+6(x+1)
=(x+1)(x+6)
i.e,x=-1 or x=-6

2006-12-29 14:20:32 · answer #8 · answered by Anonymous · 1 0

(x+1) (x+6) =0
divide first by x +6
x+1 = 0
x = -1
next divide top equation by x +1
then, x+6 =0
x= -6

2006-12-29 14:16:58 · answer #9 · answered by ignoramus 7 · 2 0

(x + 6)(x + 1) = 0
x = -6 or x = -1

2006-12-29 14:25:45 · answer #10 · answered by Johnny Handsome 2 · 1 0

fedest.com, questions and answers